Microsoft System Center 2016 service manager cookbook : discover over 100 practical recipes to help you master the art of IT service management for your organization - Asp, Anders (Packt Publishing, 2017)
Discover over 100 practical recipes to help you master the art of IT service management for your organization About This Book Unleash the capabilities of Microsoft System Center 2016 Service Manager Master the skills of configuring, deploying, managing, and troubleshooting your Service Manager 2016 This book contains practical recipes that leverage the key and newly added features and functionalities of Microsoft System Center 2016 Service Manager Who This Book Is For This book will be useful to IT professionals including SCSM administrators who want to configure and administer System Center Service Manager 2016 and understand how to solve specific problems and scenarios that arise. It will also be useful to users of Service Manager 2012 who want to learn about the new features and capabilities of the Service Manager 2016 release. It will be ideal if you have Service Manager experience as well as experience with other System Center products. What You Will Learn See a practical implementation of the ITSM framework and processes based on ITIL Deploy and configure the new Service Manager HTML5 Self-Service Portal along with Service Catalog design and configuration Get to know about Incident, Problem, and Change Management processes and configuration Get to grips with performing advanced personalization in Service Manager Discover how to set up and use automation with and within Service Manager 2016 Work with Service Manager Data Warehouse Find out what Security Roles are and how to implement them Learn how to upgrade from SCSM 2012 R2 to SCSM 2016 In Detail System Center Service Manager (SCSM) is an integrated platform that offers a simplified data center management experience by implementing best practices such as Incident Management, Service Request, and Change control to achieve efficient service delivery across your organization. This book provides you with real-world recipes that can be used immediately and will show you how to configure and administer SCSM 2016. You'll also find out how to solve particular problems and scenarios to take this tool further. You'll start with recipes on implementing ITSM frameworks and processes and configuring Service Level Agreements (SLAs). Then, you'll work through deploying and configuring the HTML5 Self-Service Portal, configuring Incident and Problem Management, and designing and configuring change and release management. You'll also learn about security roles and overall Microsoft SCSM 2016 administrat...